Is Safety in the Eye of the Beholder? Safeguards in Research With Adults With Intellectual Disability - McDonald, Katherine E.; Conroy, Nicole E.; Kim, Carolyn I.; LoBraico, Emily J.; Prather, Ellis M.; Olick, Robert S. (Journal of empirical research on human research ethics, 2016)
Human subjects research has a core commitment to participant well-being. This obligation is accentuated for once exploited populations such as adults with intellectual disability. Yet we know little about the public’s views on appropriate safeguards for this population. We surveyed adults with intellectual disability, family members and friends, disability service providers, researchers, and Institutional Review Board (IRB) members to compare views on safeguards. We found many points of convergence of views, particularly for decision-making and participation. One trend is that adults with intellectual disability perceive greater safety in being engaged directly in recruitment, and recruitment by specific individuals. Researchers and IRB members need to consider community views to facilitate the safe and respectful inclusion of adults with intellectual disability.